Association between Helicobacter pylori Infection and Risk of Osteoporosis in Elderly Taiwanese Women with Upper Gastrointestinal Diseases: A Retrospective Patient Record Review - Shih-Chun Lin; Malcolm Koo; Kun-Wei Tsai (Gastroenterology Research and Practice)
Introduction. Helicobacter pylori (H. pylori) infection could lead to chronic local and systemic immune response. The resulting increase in proinflammatory cytokines could affect bone resorption and might increase the risk of osteoporosis. This study aimed to investigate the association between H. pylori infection and osteoporosis in elderly female patients with upper gastrointestinal diseases. Methods. A retrospective patient record review study was conducted in a regional teaching hospital in south Taiwan. Relevant information on female patients aged 65 and over who were diagnosed with diseases of esophagus, gastric ulcer, or duodenal ulcer during January 2008 to December 2010 were abstracted. Association between H. pylori infection and osteoporosis was evaluated using multivariate logistic regression analysis. Results. Of the 365 patients with a mean age of 77.3 years, 77 (21.1%) had H. pylori infection and 101 (27.7%) had been diagnosed with osteoporosis. Multivariate logistic regression analysis revealed that osteoporosis was significantly associated with H. pylori infection (adjusted odds ratio = 2.03, 95% confidence interval = 1.14–3.62) after adjusting for age group, body mass index group, and use of proton pump inhibitor. Conclusion. Osteoporosis was found to be associated with H. pylori infection in Taiwanese female patients with upper gastrointestinal diseases. Further studies with information on potential confounders are needed to confirm the association.